Associations between autoimmune conditions and hepatobiliary cancer risk among elderly US adults. Issue 4 (8th November 2018) - McGee, Emma E.; Castro, Felipe A.; Engels, Eric A.; Freedman, Neal D.; Pfeiffer, Ruth M.; Nogueira, Leticia; Stolzenberg‐Solomon, Rachael; McGlynn, Katherine A.; Hemminki, Kari; Koshiol, Jill
Abstract : Growing evidence suggests that people with autoimmune conditions may be at increased risk of hepatobiliary tumors. In the present study, we evaluated associations between autoimmune conditions and hepatobiliary cancers among adults aged ≥66 in the United States. We used Surveillance, Epidemiology, and End Results (SEER)‐Medicare data (1992–2013) to conduct a population‐based, case–control study. Cases ( n = 32, 443) had primary hepatobiliary cancer. Controls ( n = 200, 000) were randomly selected, cancer‐free adults frequency‐matched to cases by sex, age and year of selection. Using multivariable logistic regression, we calculated odds ratios (ORs) and 95% confidence intervals (CIs) for associations with 39 autoimmune conditions identified via Medicare claims. We also conducted separate analyses for diagnoses obtained via inpatient versus outpatient claims. Sixteen conditions were associated with at least one hepatobiliary cancer. The strongest risk estimates were for primary biliary cholangitis with hepatocellular carcinoma (OR: 31.33 [95% CI: 23.63–41.56]) and primary sclerosing cholangitis with intrahepatic cholangiocarcinoma (7.53 [5.73–10.57]), extrahepatic cholangiocarcinoma (5.59 [4.03–7.75]), gallbladder cancer (2.06 [1.27–3.33]) and ampulla of Vater cancer (6.29 [4.29–9.22]). Associations with hepatobiliary‐related conditions as a group were observed across nearly all cancer sites (ORs ranging from 4.53 [95% CI: 3.30–6.21] for extrahepatic cholangiocarcinoma to 7.18 [5.94–8.67] for hepatocellular carcinoma). Restricting to autoimmune conditions diagnosed via inpatient claims, 6 conditions remained associated with at least one hepatobiliary cancer, and several risk estimates increased. In the outpatient restricted analysis, 12 conditions remained associated. Multiple autoimmune conditions are associated with hepatobiliary cancer risk in the US Medicare population, supporting a shared immuno‐inflammatory etiology to these cancers. Abstract : What's new? Growing evidence suggests that people with autoimmune conditions may be at increased risk of hepatobiliary tumors. This large, longitudinal study investigated associations between hepatobiliary cancers and 39 autoimmune conditions. There was a 1.1‐ to 31.3‐fold increased risk of hepatobiliary cancer after diagnosis of a range of different autoimmune diseases, and novel associations were observed. The magnitude of associations was particularly strong for primary biliary cholangitis, primary sclerosing cholangitis, pure red cell aplasia and immune thrombocytopenic purpura. Findings support an immuno‐inflammatory etiology. Further research is needed to assess the need for additional cancer monitoring in individuals with certain autoimmune conditions.